Respuesta :
Let x = 2y. Then we want to show
sin(6y) + sin(4y) - sin(2y) = 4 sin(2y) cos(y) cos(3y)
Recall the angle sum identities,
sin(x ± y) = sin(x) cos(y) ± cos(x) sin(y)
cos(x ± y) = cos(x) cos(y) ∓ sin(x) sin(y)
which lets us write
sin(6y) = sin(4y + 2y) = sin(4y) cos(2y) + cos(4y) sin(2y)
sin(4y) = sin(2y + 2y) = 2 sin(2y) cos(2y)
cos(4y) = cos(2y + 2y) = cos²(2y) - sin²(2y)
Ultimately, we use these identities to rewrite the left side as
sin(6y) + sin(4y) - sin(2y)
= 2 (sin(4y) cos(2y) + cos(4y) sin(2y)) + 2 sin(2y) cos(2y) - sin(2y)
= 2 sin(2y) cos²(2y) + (cos²(2y) - sin²(2y)) sin(2y) + 2 sin(2y) cos(2y) - sin(2y)
Notice the underlined common factor of sin(2y). If we remove this from both sides of the identity we want to prove, then it remains to show that
2 cos²(2y) + (cos²(2y) - sin²(2y)) + 2 cos(2y) - 1 = 4 cos(y) cos(3y)
or
3 cos²(2y) - sin²(2y) + 2 cos(2y) - 1 = 4 cos(y) cos(3y)
Recall the Pythagorean identity,
cos²(x) + sin²(x) = 1
which lets us write
3 cos²(2y) - sin²(2y) + 2 cos(2y) - 1
= 3 cos²(2y) - (1 - cos²(2y)) + 2 cos(2y) - 1
= 4 cos²(2y) + 2 cos(2y) - 2
= 2 (2 cos²(2y) + cos(2y) - 1)
= 2 (2 cos(2y) - 1) (cos(2y) + 1)
Recall the half-angle identity for cosine,
cos²(x/2) = 1/2 (1 + cos(x))
which means
cos(2y) + 1 = 2 • 1/2 (1 + cos(2y)) = 2 cos²(y)
and so
2 (2 cos(2y) - 1) (cos(2y) + 1)
= 4 (2 cos(2y) - 1) cos²(y)
= 4 cos(y) (2 cos(2y) - 1) cos(y)
Now notice the underlined factor of 4 cos(y), which also appears in the right side of the identity we want to prove. Eliminate this term and all that's left is to show that
(2 cos(2y) - 1) cos(y) = cos(3y)
which follows from a combination of the identities I mentioned above:
(2 cos(2y) - 1) cos(y)
= 2 cos(2y) cos(y) - cos(y)
= 2 • 1/2 (cos(2y + y) + cos(2y - y)) - cos(y)
= (cos(3y) + cos(y)) - cos(y)
= cos(3y)
as required.
Trigonometric identities involve equations that use the trigonometric functions that are true for all variables in the equation
The identity is given as:
[tex]\sin(3x) + \sin(2x) - \sin(x) = 4\sin(x)\cos(\frac x2)\cos(\frac{3x}{2})[/tex]
Let x = 2y.
So, we have:
[tex]\sin(6y) + \sin(4y) - \sin(2y) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Expand
[tex]\sin(4y + 2y) + \sin(2y + 2y) - \sin(2y) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Expand the identities using the angle sum identities,
[tex]\sin(4y)\cos(2y) + \cos(4y)\sin(2y) + 2\sin(2y)\cos(2y) - \sin(2y) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Expand cos(4y) and sin(4y)
[tex]2\sin(2y)\cos^2(2y) + [\cos^2(2y) - \sin^2(2y)]\sin(2y) + 2\sin(2y)\cos(2y) - \sin(2y) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Factor out sin(2y)
[tex]\sin(2y)[2\cos^2(2y) + \cos^2(2y) - \sin^2(2y) + 2\cos(2y) - 1] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Evaluate the like terms
[tex]\sin(2y)[3\cos^2(2y) - \sin^2(2y) + 2\cos(2y) - 1] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Substitute
[tex]\sin^2(2y) = 1 - \cos^2(2y)[/tex]
[tex]\sin(2y)[3\cos^2(2y) - 1 + \cos^2(2y) + 2\cos(2y) - 1] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Evaluate the like terms
[tex]\sin(2y)[4\cos^2(2y) - 1 + 2\cos(2y) - 1] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
[tex]\sin(2y)[4\cos^2(2y) + 2\cos(2y) - 2] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Factor out 2
[tex]2\sin(2y)[2\cos^2(2y) + \cos(2y) - 1] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Expand
[tex]2\sin(2y)[2\cos^2(2y) +2\cos(2y) - \cos(2y) - 1] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Factorize
[tex]2\sin(2y)[2\cos(2y)( \cos(2y) + 1) -1( \cos(2y) + 1)] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Factor out cos(2y) + 1
[tex]2\sin(2y)[( 2\cos(2y) - 1)( \cos(2y) + 1)] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
By half identity, we have:
[tex]\cos\²(\frac x2) = \frac 12 (1 + \cos(x))[/tex]
Multiply both sides by 2
[tex]2\cos\²(\frac x2) = (1 + \cos(x))[/tex]
Replace x with 2y
[tex]2\cos\²(y) = 1 + \cos(2y)[/tex]
So, we have:
[tex]2\sin(2y)[( 2\cos(2y) - 1)( 2\cos^2(y))] = 4\sin(2y)\cos(y)\cos(3y)[/tex]
[tex]4\sin(2y)(2 \cos(2y) - 1)(\cos^2(y)) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Factor out cos(y)
[tex]4\sin(2y)(\cos(y)(2 \cos(2y) - 1)(\cos(y)) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Expand
[tex]4\sin(2y)(\cos(y)(2 \cos(2y)\cos(y) - \cos(y)) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Using the half identity, we have:
[tex]4\sin(2y)(\cos(y)(2 * \frac 12 *\cos(2y + y) + \cos(2y - y) - \cos(y)) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
[tex]4\sin(2y)(\cos(y)(\cos(3y) + \cos(y) - \cos(y)) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
[tex]4\sin(2y)\cos(y)\cos(3y) = 4\sin(2y)\cos(y)\cos(3y)[/tex]
Recall that:
x = 2y
So, we have:
[tex]4\sin(x)\cos(\frac x2)\cos(\frac {3x}2) = 4\sin(x)\cos(\frac x2)\cos(\frac {3x}2)[/tex]
Both sides of the equations are the same.
Hence, the identity [tex]\sin(3x) + \sin(2x) - \sin(x) = 4\sin(x)\cos(\frac x2)\cos(\frac{3x}{2})[/tex] has been proved
Read more about trigonometry identity at:
https://brainly.com/question/7331447